Respuestas

  • Usuario de Brainly
2014-03-06T04:30:34+01:00


utilizamos la formula
              [-b +-√(b² -4ac)]        a= 2      b= 7  c=3
senx = ----------------------------
                     2a

           [  -7 +-√(7² -4*2*3)]
senx = ----------------------------
                     2*2

           [ -7+-√(49-24)]
senx = -----------------------
                   4

             -7+- √25
senx = -----------------
                  4
  
           -7 +-5
senx = ---------
               4

           -7+5
senx =----------
             4
senx= -2/4
senx = -1/2
senx = - 0.5
x = sen^(-1)(-0,5)
x= -30°


senx = -7-5/4
sen x = -12/4
senx = -3  este no existe